DOI: 10.31274/etd-180810-1041
|View full text |Cite
|
Sign up to set email alerts
|

Grassland bird response to enhanced vegetation diversity in restoration plantings in the Spring Run Complex of northwestern Iowa

Abstract: Loss of habitat is one of the primary factors affecting population declines of grassland birds, and recovery efforts have focused on increasing the amount of grassland habitat in the landscape. Assessing the value of habitat restorations for grassland birds is an essential component of grassland bird conservation. We compared grassland bird habitat use, reproductive success, nestling growth rates, nestling baseline corticosterone, and blood glucose levels among restored grasslands planted with seed mixes of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…In this study, sedge wrens were more abundant in tallgrass and mixed-grass prairie units that were rested for more than five growing seasons than in managed NPAM units. Similar to this study, high vertical heightdensity or vertical obstruction was identified as an important habitat feature for sedge wrens by Sample (1989), Delisle andSavidge (1997), andVogel (2011). Sedge wren preference for grasslands with greater litter depth also was noted by Delisle and Savidge (1997), Bakker and others (2002), Renfrew and Ribic (2002), Pillsbury (2010), and Vogel (2011).…”
Section: Sedge Wren (Cistothorus Platensis)supporting
confidence: 78%
“…In this study, sedge wrens were more abundant in tallgrass and mixed-grass prairie units that were rested for more than five growing seasons than in managed NPAM units. Similar to this study, high vertical heightdensity or vertical obstruction was identified as an important habitat feature for sedge wrens by Sample (1989), Delisle andSavidge (1997), andVogel (2011). Sedge wren preference for grasslands with greater litter depth also was noted by Delisle and Savidge (1997), Bakker and others (2002), Renfrew and Ribic (2002), Pillsbury (2010), and Vogel (2011).…”
Section: Sedge Wren (Cistothorus Platensis)supporting
confidence: 78%
“…In eastern Nebraska and western Iowa, Sedge Wren density was lowest in warm-season grasslands planted with a high-diversity seeding mixture and highest in warm-season grasslands planted with a low-diversity seeding mixture (Cox and others, 2014). In Iowa, Sedge Wren density was higher in grasslands planted to cool-season, tame grass species than in newly planted grasslands seeded to warm-season, native grass species (Vogel, 2011). Sedge Wren density did not differ, however, among several other plantings, including mature stands of native, warm-season grasslands and grasslands planted to a high-diversity mix of over 40 species of native grasses and forbs (Vogel, 2011).…”
Section: Suitable Habitatmentioning
confidence: 91%
“…In Iowa, Sedge Wren density was higher in grasslands planted to cool-season, tame grass species than in newly planted grasslands seeded to warm-season, native grass species (Vogel, 2011). Sedge Wren density did not differ, however, among several other plantings, including mature stands of native, warm-season grasslands and grasslands planted to a high-diversity mix of over 40 species of native grasses and forbs (Vogel, 2011). Within CRP filter strips in Iowa, Sedge Wren density did not differ between strips planted to cool-season plant mixtures and strips planted to warm-season mixtures (Henningsen and Best, 2005).…”
Section: Suitable Habitatmentioning
confidence: 94%
See 2 more Smart Citations